Limited carbon and mineral nutrient gain from mycorrhizal fungi by adult Australian Orchids - Sommer, J.; Pausch, J.; Brundrett, M.; Dixon, Kingsley; Bidartondo, M.; Gebauer, G. (2012)
Premise of the study: In addition to autotrophic and fully mycoheterotrophic representatives, the orchid family comprises species that at maturity obtain C and N partially from fungal sources. These partial mycoheterotrophs are often associated with fungi that simultaneously form ectomycorrhizas with trees. This study investigates mycorrhizal nutrition for orchids from the southwestern Australian biodiversity hotspot. Methods: The mycorrhizal fungi of 35 green and one achlorophyllous orchid species were analyzed using molecular methods. Nutritional mode was identified for 27 species by C and N isotope abundance analysis in comparison to non-orchids from the same habitat. As a complementary approach, 13CO2 pulse labeling was applied to a subset of six orchid species to measure photosynthetic capacity. Key results: Almost all orchids associated with rhizoctonia-forming fungi. Due to much higher than expected variation within the co-occurring nonorchid reference plants, the stable isotope approach proved challenging for assigning most orchids to a specialized nutritional mode; therefore, these orchids were classified as autotrophic at maturity. The 13CO2 pulse labeling confirmed full autotrophy for six selected species. Nonetheless, at least three orchid species (Gastrodia lacista, Prasophyllum elatum, Corybas recurvus) were identified as nutritionally distinctive from autotrophic orchids and reference plants Conclusions: Despite the orchid-rich flora in southwestern Australia, partial mycoheterotrophy among these orchids is less common than in other parts of the world, most likely because most associate with saprotrophic fungi rather than ectomycorrhizal fungi.